1997
DOI: 10.1023/a:1019014701674
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Methanol Synthesis over Cu/ZnO Catalysts Prepared by Ball MillingHuang, L.; Kramer, G.J.; Wieldraaijer, W.; Brands, D.S.; Poels, E.K.; Castricum, H.L.; Bakker, H. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…A Cu/ZnO sample milled in vacuum had been investigated previously [11], showing both low Cu metal area and low BET surface area. The Cu 0 specific surface areas of all milled samples discussed here are increased by more than one order of magnitude compared to their unmilled precursors.…”
Section: Surface Areamentioning
confidence: 99%
See 1 more Smart Citation
“…A Cu/ZnO sample milled in vacuum had been investigated previously [11], showing both low Cu metal area and low BET surface area. The Cu 0 specific surface areas of all milled samples discussed here are increased by more than one order of magnitude compared to their unmilled precursors.…”
Section: Surface Areamentioning
confidence: 99%
“…In order to achieve high activity a good intimate mixture of Cu and ZnO must be obtained [9,10]. The ultimate structure and activity of the mechanochemically prepared catalyst show a strong dependency on the milling atmosphere [11]. A mixture of Cu and ZnO milled in vacuum was hardly active, whereas this mixture milled in ambient air was as active as a coprecipitated catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Several methods have been developed for the synthesis of Cu/ZnO nanocomposites involving organometallic [35] or mechanochemical routes. [36] Recently, the synthesis of Cu@ZnO core-shell nanocomposites by solvated metal atom dispersion (SMAD) has been reported. [37] The technique, originally developed by Klabunde and co-workers, [38] consists of cocondensation of substrate vapors together with a cosolvent or stabilizing agent, in this case 2-butanone, under high vacuum onto a target that is maintained at liquid nitrogen temperature.…”
mentioning
confidence: 99%
“…Over the past decades, grinding-assisted catalyst synthesis has attracted tremendous attention by providing a much simpler, waste-free, easily scalable and energyefficient technique for fabrication of new catalytic materials with improved and/or novel physical and chemical properties as compared to conventional methods [19][20][21][22][23][24][25]. Very recently, we have shown that highly effective Cu/ZnO materials with favorable surface and structural properties for methanol steam reforming can be prepared via a simple yet versatile technique based on soft reactive grinding (SRG), removing the need of vast amount of water and the formation of large amount of wastes [26].…”
Section: Introductionmentioning
confidence: 99%